Inter-organ transport of secologanin allows assembly of monoterpenoid indole alkaloids in a Catharanthus roseus mutant. (March 2019) - Kidd, Trevor; Easson, Michael LAE.; Qu, Yang; De Luca, Vincenzo
Abstract: The medicinal value of the monoterpenoid indole alkaloids (MIAs) such as 3′, 4′-anhydrovinblastine, as well as their chemical complexity have stimulated extensive efforts to understand the biochemical and molecular pathways involved in their biosynthesis in plants such as Catharanthus roseus, Rawvolfia serpentina and others. Ethyl methane sulphonate (EMS) mutagenesis has been used successfully together with simple MIA thin layer chromatography screening to identify C. roseus mutants with altered MIA profiles. This study describes the isolation of very low iridoid and MIA containing C. roseus mutant (M2-1582) that accumulates MIAs when the plant is provided with secologanin by feeding mutant roots or by grafting the mutant scion onto wild type roots. The observed low iridoid and MIA content was correlated with lowered expression of BIS1/BIS2 transcription factors and several genes involved in secologanin biosynthesis that are expressed in internal phloem parenchyma cells of leaves. When exogenous secologanin was applied to the roots of the mutant plant, secologanin levels rose more than 13-fold, while two major MIAs catharanthine and vindoline rose more than 8- and 4- fold, respectively. Grafting the mutant on WT stocks led to 27-, 11- and 27-fold increases in secologanin, catharanthine and vindoline, respectively in leaves of the scion one week after graft initiation. Other minor MIAs (serpentine, anhydrovinblastine, vindolidine, deacetylvindoline, tabersonine and 16-methoxytabersonine) that were not detected in the mutant, became detectable in leaves of the scion. These results provide strong evidence for a secologanin transport mechanism that mobilizes this iridoid between different plant organs in C. roseus and that secologanin transport to the mutant across the graft union permits the formation of MIAs in leaves of the mutant. Graphical abstract: Highlights: A low (iridoid) secologanin Catharanthus roseus mutant contains almost no MIAs. The mutant is down-regulated in transcription factors and iridoid pathways genes. The mutant will take up secologanin through roots to make MIAs. Grafting of WT roots to mutant scion allows transport of secologanin into the scion. The transported secologanin is converted into MIAs in the mutant scion.